2020
DOI: 10.21203/rs.3.rs-38320/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“It’s really no more difficult than putting on fluoride varnish”: A qualitative exploration of dental professionals’ views of silver diamine fluoride for the management of carious lesions in children

Abstract: Abstract Background: Despite evidence that Silver Diamine Fluoride (SDF) can be effective in managing carious lesions in primary teeth, there is still limited use the UK. This study explored dental professionals’ views and experiences of using SDF for managing carious lesions in children. In addition, it explored what they perceived to be the advantages, disadvantages, barriers and enablers to the use of SDF in practice.Methods: Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…33 This demerit of SDF is main barrier for universal adaptation among dentists but keeping in view of the pandemic of COVID-19, we can see increased use of SDF in management of dentinal caries throughout the world. 42 Efforts are being made to reduce the black discoloration by incorporating nano-silver particles and application of Potassium Iodide solution over SDF. 43 The major limitation of this study was its short duration to justify the effectiveness of both the agents based on caries arrest, preventive fraction and the single-blind nature of the study, which may increase the risk of reporting and measurement bias.…”
Section: Discussionmentioning
confidence: 99%
“…33 This demerit of SDF is main barrier for universal adaptation among dentists but keeping in view of the pandemic of COVID-19, we can see increased use of SDF in management of dentinal caries throughout the world. 42 Efforts are being made to reduce the black discoloration by incorporating nano-silver particles and application of Potassium Iodide solution over SDF. 43 The major limitation of this study was its short duration to justify the effectiveness of both the agents based on caries arrest, preventive fraction and the single-blind nature of the study, which may increase the risk of reporting and measurement bias.…”
Section: Discussionmentioning
confidence: 99%
“…An interview schedule was developed to examine acceptability of SDF from a parent and child perspective, using age-appropriate language (Additional le 1). This interview schedule was informed by the literature as well as previous work conducted by the authors, exploring Dental Care Professionals' acceptability of SDF [7]. Using clinical photographs of patients before and after SDF treatment (Additional le 2), questions were focused on the acceptability of SDF, together with factors that in uence decision-making regarding other treatment options.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, one side effect is that the carious lesion is stained black. It has been suggested that this staining could be a barrier to its use for some parents, especially for anterior teeth [7]. Yet, there is other evidence to suggest that parents may view this discoloration as a positive sign that the treatment has been effective [2].…”
Section: Introductionmentioning
confidence: 99%